Presencia de estro post-parto en el murciélago frugivoro carollia perspicillata (1988)
The occurrence and possibility of post-partum oestrum of the species Carollia perspicillata was studied in one group of 25 bats in cautivity. The study was carried out, during the inmediate post-partum by the obtention of daily vaginal smears along 30 days to define the onset of oestrum by vaginal cytology. At the end of 30 days, the females were sacrified in order to carry out complete histological studies of reproductive tracts. The vaginal smears clearly showed four phases in the oestral cycle: proestrus, estrus, postestrus and diestrus. The study showed that the lactating females accept the males. Which was confirmed by the presence of spermatozoa in the vaginal smears and in the uterine slides. The histological study ovary showed the presence of follicles with a fairly large antrum, oestrum with mature follicles, recent corpus luteum which showed ovulation and early pregnant uterus. The above mentioned findings confirm the existence of post- partum oestrum in Carollia perspicillata.